Expert opinions and clinical experiences with chlormethine gel as maintenance treatment for patients with mycosis fungoides - Geskin, Larisa; Querfeld, Christiane; Hodak, Emmilia; Nikbakht, Neda; Papadavid, Evangelia; Ardigò, Marco; Wehkamp, Ulrike; Bagot, Martine (Frontiers in Medicine, 2024)
Maintenance treatment can be recommended for patients with mycosis fungoides (MF) whose disease responds to primary treatment. While positive outcomes have been observed in small studies with maintenance therapy, there is a lack of practical guidelines and agreement on when and how maintenance therapy for MF should be approached. In this article, we discuss expert opinions and clinical experiences on the topic of maintenance therapy for patients with MF, with a focus on chlormethine gel. Ideally, patients should have a durable response before initiating maintenance therapy. The definition of and required duration of durable response are topics that are open to debate and currently have no consensus. Chlormethine gel has several attributes that make it suitable for maintenance therapy; it can be easily applied at home, can be combined with other treatment options for maintenance, and has a manageable safety profile. Chlormethine gel as maintenance therapy can be applied at decreasing frequencies after active treatment with chlormethine gel or other therapies until the minimally effective dose is reached. Patients generally tend to adhere well to chlormethine gel maintenance regimens and may remain on treatment for several years. The experiences described here may be useful for clinicians when deciding on maintenance treatment regimens for their patients. Development of guidelines based on clinical trial outcomes will be important to ensure the most effective maintenance treatment strategies are used for patients with MF.